2014
DOI: 10.1111/radm.12069
|View full text |Cite
|
Sign up to set email alerts
|

The fit between technological innovation and business model design for firm growth: evidence from China

Abstract: How does technological innovation fit with business model design to jointly impact firm growth? Given the increasingly salient role of business model, extant literature provides little answer to this question. This study builds a theoretical model based on technological innovation literature, business ecosystem theory, and business model literature to investigate this issue. This study finds that exploitative innovation and exploratory innovation fit with different business model designs to promote firm growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 78 publications
2
108
0
Order By: Relevance
“…Zott et al () found a particular research stream that focuses on how business models help to commercialize technology. Recent research has shown the importance of aligning technological developments with an adequate business model in order to be successful (Wei et al, ). Besides the role of business models for new technologies, new technology is required in order to reconfigure the business model.…”
Section: Scale Developmentmentioning
confidence: 99%
“…Zott et al () found a particular research stream that focuses on how business models help to commercialize technology. Recent research has shown the importance of aligning technological developments with an adequate business model in order to be successful (Wei et al, ). Besides the role of business models for new technologies, new technology is required in order to reconfigure the business model.…”
Section: Scale Developmentmentioning
confidence: 99%
“…Commitment to social responsibility Our company has a formal social responsibility strategy Our company contributes to campaigns and projects that promote the well-being of society Our company participates in activities that aim to protect and improve the quality of the natural environment Our company has a policy about social responsibility towards employees Turker (2009) Social innovation Our company invests in research and development projects to improve the well-being of society in the future We strive to improve people's lives through the new products and services we develop We strive to initiate improvements in society through the new products and services we develop We use new technologies to find solutions to social needs Brammer et al (2011) and Wei et al (2014) Reporting on social responsibility We communicate our strategy on social responsibility to our stakeholders in a transparent way We advertise our environmental efforts We communicate our strategy on social responsibility to all employees in a transparent way Brammer et al (2011) Customer acceptance Our customers were more satisfied than our competitors' customers We created more value for customers than our competitors We fulfilled customers' needs better than our competitors did We were better able to retain existing customers than our competitors Moorman and Rust (1999) and Page (1993, 1996) All survey items were phrased as statements and respondents were asked to select a response from 1 (disagree) to 5 (agree).…”
Section: Survey Items Referencesmentioning
confidence: 99%
“…Moreover, although the limited quantitative research demonstrates that business model innovation helps improve organizational performance measures such as profitability and innovativeness (e.g., Aspara, Hietanen, & Tikkanen, ; Bock, Opsahl, George, & Gann, ; Denicolai, Ramirez, & Tidd, ; Giesen, Berman, Bell, & Blitz, ; Wei, Yang, Sun, & Gu, ; Zott & Amit, ), significant gaps remain. These gaps include absence of clear constructs in business models and the causal relationships between them, ambiguity as to how business model innovation is causally linked to antecedents and performance, and poor understanding of the contingency and moderating variables (Foss & Saebi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although the limited quantitative research demonstrates that business model innovation helps improve organizational performance measures such as profitability and innovativeness (e.g., Aspara, Hietanen, & Tikkanen, 2010;Bock, Opsahl, George, & Gann, 2012;Denicolai, Ramirez, & Tidd, 2014;Giesen, Berman, Bell, & Blitz, 2007;Wei, Yang, Sun, & Gu, 2014;Zott & Amit, 2007), significant gaps remain.…”
Section: Introductionmentioning
confidence: 99%